The fast track land reform programme and its effect on the loss of forests: the case of the Mafungabusi Forest Reserve in Zimbabwe - Musananguro, M.; Ali, F.; Mlambo, R.; Masarira, T. P. (Commonwealth Forestry Association, 2022)
The Fast Track Land Reform Programme (FTLRP) resulted in the loss of forest reserves and biodiversity. Co-management of forest reserves with resettled farmers is required for sustainability. Remote sensing and GIS plays an important role in the management and monitoring of forests. Multiplicity of legal instruments and institutional arrangements in forest management promotes forest loss and misuse. Sustainable management and enforcement of legal instruments on forest reserves is required to combat effects of climate change and desertification. SUMMARY Land reform in Zimbabwe, commonly known as the Fast Track Land Reform Programme (FTLRP), was established in early 2000. Since the inception of the FTRLP, loss of forests and biodiversity has been on the rise. In this paper, an analysis of the rate of forest loss pre-FTLRP, during and post-FTLRP to date (1995–2019) is presented for the Mafungabusi Forest Reserve. Data were collected from semi-structured questionnaires, interviews, satellite imagery and fieldwork. Land Cover, Land-Use Change Maps were obtained from supervised classification of satellite imagery and regression graphs for the rate of change of forest area were also obtained. Results show that the forested areas decreased at a rate of 308 ha per year (2.4%) during the FTLRP and at a rate of 481 ha per year (5.2%) post FTLRP. The inception of FTLRP and the withdrawal of funds to support the Community Involvement in Forest Management (CIFM) resulted in forest loss as the population grew and demand for land increased. Given the current rate of forest loss, the Mafungabusi Forest will probably disappear in the next 20 years if no measures are taken to reduce the rate of forest loss. Thus, there is need for the Zimbabwe Forestry Commission, Environmental Management Agency and other relevant stakeholders to engage resettled farmers in sustainable co-management of natural resources. Such efforts will help in combating effects of climate change and conserving biodiversity.